Vérité et justice dans les romans francophones RD congolais de l’extrême contemporain - Desorbay, Bernadette (Ponti/Ponts, 2024)
Advances in postcolonial studies aimed at deconstructing Western logocentrism have opened up literary research to new hermeneutical paradigms in the analysis of the representation of ongoing violence in sub-Saharan Africa. Research on the DR Congo deserves to be more closely examined in that perspective. Generally speaking, it has become a current issue now to implement, in the humanities, an epistemological rethinking of imaginaries for a knowledge connected to a global scale according to an approach that would not lose sight of the need to oppose the persistent silence on human rights. This issue will be discussed from the Francophone DR Congolese novels of the years 2010-2020, by In Koli Jean Bofane, Blaise Ndala and, more particularly, by Sinzo Aanza and Fiston Mwanza Mujila.